ANALISIS USAHATANI JAGUNG PADA LAHAN KERING DI KECAMATAN LIMBOTO KABUPATEN GORONTALO - Ikbal Bahua (Jurnal Penyuluhan, 2008)
The objectives of this action research are 1) to describe the structure of expenses of the maize farming at dry farming system, 2) to describe the production and farmers earnings at maize dry farming system. Research Method used is survey method, consisted of the survey of primary and secondary data. Variable perceived is maize farmer labouring maize crop to fulfill its requirement, maize farming conducted at dry farming, produce the maize farming, earnings of maize farming, medium produce, and good labour of labour in and also household outdoors labour of doorstep. Intake sampel conducted by purposive summed uply is farmer becoming sampel is 30 people deputize the population of maize farmer of counted 150 people. Result of research of there are ratio difference of between production cost and production rate at maize farming of maize of hibrida and composite maize farming in dry farming with the value R/C ratio more than 1. For the earnings of, farmer planting compared to higher maize hibrida of farmer earnings planting composite maize with the comparison ratio is 2,60.